Obstacles in Marketing Comprehensive Automobile Insurance Policy: بحث أستطلاعي في شركة التأمين الوطنية (Journal of Accounting and Financial Studies ( JAFS ), 2013)
Comprehensive automobile insurance is considered as an important branches in the portfolio of National Insurance Company in Iraq .Due to the continous accidents the company is endeavouring to   this market.    The company faces several obstacles and limitations in marketing the policies of this portfolio due to certain factors and influences beyond the control of the company and others internal mainly connected with the reduction of the marketing programmes of the company .    The target of this study is  to focus the light  upon the interal factors which can be gorerned by the company,confronted and solved.